The Influence of E-WOM on Travel Intention among Foreign Students in Malaysia: Does Gender Really Matter? - Krishnapillai, Gengeswari; Ying, Kwok See (International Review of Management and Marketing, 2017)
As an attractive educational hub within this region, Malaysia currently accommodates an enormous number of foreign students. These students are known for their inclination towards tour and travel activities during their spare time. In view of the potential contribution of foreign students’ travel activities towards the nation, this study attempts to examine the tour behaviour among foreign students in Malaysia. This study specifically focuses on the foreign students’ travel intention and possible influences of Electronic-Word-of-Mouth (E-WOM) on their travel intention. In addition, this study intends to determine the influence of gender differences on the impact of the E-WOM towards students’ travel intention. The foreign students pursuing their tertiary education in Limkokwing University located at Cyberjaya, Malaysia comprise the population of this study. Snowball sampling was used to draw 500 representative elements for the study’s self-administrated survey. Structural equation modelling (SEM) analysis was used to analyse the data collected. Findings revealed that E-WOM significantly influenced the foreign students’ intention to travel in Malaysia. Nonetheless, an insignificant moderation effect of gender on the relationship between E-WOM and Travel Intention was found. Following a detailed discussion on the findings obtained, this study presented several managerial implications alongside recommendation for future researches. Keywords: Travel intention, electronic word of mouth, gender differences JEL Classifications: C30, M310